Promoting Environmental Awareness Using Comic Books for Children Aged 5-6 - Hapidin; Utara, Adiis Retna; Utami, Ade Dwi (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Environmental awareness is a behavior reflected in a person who is always mindful of their actions so that they do not harm the environment. This behavior is important because environmental damage is increasing due to global climate change and extreme weather. Early childhood education plays an important role in promoting environmental awareness as early as possible. This study aims to identify the problems related to environmental awareness in children and provide an alternative solution to promote environmental awareness in children aged five to six years old. Interviews conducted with two early childhood education teachers in a kindergarten in South Bekasi found that children still have low environmental awareness and the need for learning media to help promote it. The use of comic books as a teaching strategy in early childhood education is still not common as comics are often seen as shallow and lacking educational value. This study reviews literature concerning the use of comic books as learning media in educational settings. By applying descriptive qualitative method, the results show that comic books have the potential to be used as a learning media in early childhood education. This finding is expected to serve as a reference for using comic books in learning to promote environmental awareness for children aged five to six years old.